2008
DOI: 10.1002/uog.5191
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of classification of breast ultrasound findings based on criteria used for BI‐RADS

Abstract: Objective To assess the accuracy of categorization of breast ultrasound findings based on scoring for malignancy using the sonographic breast imagingreporting and data system (BI-RADS). Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 17 publications
3
39
2
Order By: Relevance
“…Lesion less than 4a is considered as a benign lesion while lesion more than 4a is considered as malignant lesions. The routine sonographic manifestations of level 4 BI-RAD breast lesions tend to have a certain degree of overlapping and are sometimes difficult to judge [12][13][14]. Thus, it is difficult to identify the nature of such lesions in clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesion less than 4a is considered as a benign lesion while lesion more than 4a is considered as malignant lesions. The routine sonographic manifestations of level 4 BI-RAD breast lesions tend to have a certain degree of overlapping and are sometimes difficult to judge [12][13][14]. Thus, it is difficult to identify the nature of such lesions in clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is difficult to identify the nature of such lesions in clinic. Screening US, however, has been devaluated due to its operator dependency, dubious cost-effective (ness, and relatively high false positive rate [13][14][15][16]. In this study, combined MG and US, the category was determined by BI-RADS 1-4a category was MG and US alone both no more than 4a, however, 4b-5a cacategory was considered as the score of MG and US both more than 4a; PPV, positive predictive values; NPV, negative predictive values.…”
Section: Discussionmentioning
confidence: 99%
“…Gray-scale sonography has become an essential medical tool in the detection and differentiation of breast tumor (22)(23)(24)(25)(26)(27)(28)(29)(30), showing higher sensitivity for breast tumor compared to mammography before surgery (gray-scale sonography, 88%; mammography, 69%) (31). Balu-Maestro et al (15) found that gray-scale sonography was more sensitive than mammography for detecting benign lesions after BCT, but showed almost equal ability to detect IBTR (radiography, 95.5%; sonography, 90.0%).…”
Section: Discussionmentioning
confidence: 99%
“…The American College of Radiology developed a breast imaging reporting and data system (BI-RADS) lexicon for breast sonography to standardize the characterization of breast lesions (22). Several studies have reported that scoring findings from breast ultrasonography based on the criteria used for BI-RADS allowed highly accurate differentiation of benign structures from malignant breast tumor (23)(24)(25). The present study compared the accuracy of PDS and grayscale sonography standardized by BI-RADS for differentiating scar formation and IBTR after BCT.…”
Section: Introductionmentioning
confidence: 98%
“…Access to prior images reduces the rates of false positives and unnecessary follow-up imaging [49], and peer-review and peer-learning improve interpretation quality [50]. Of the RADS tools, diagnostic accuracy has been studied most using BI-RADS ® which has consistently been shown to improve accuracy and the quality of interpretations in breast imaging [49,[51][52][53][54][55][56].…”
Section: Interpretation and Reportingmentioning
confidence: 99%